Heat transfer of horizontal parallel pipe ground heat exchanger and experimental verification - Demir, Hakan; Koyun, Ahmet; Temir, Galip (PERGAMON-ELSEVIER SCIENCE LTD, 2009)
The ground heat exchangers (GHE) consist of pipes buried in the soil and is used for transferring heat between the soil and the heat exchanger pipes of the ground source heat pump (GSHP). Because of the complexity of the boundary conditions, the heat conduction equation has been solved numerically using alternating direction implicit finite difference formulation. A software was developed in MATLAB environment and the effects of solution parameters on the results were investigated. An experimental study was carried out to test the validity of the model. An experimental GSHP system is installed at Yildiz Technical University Davupasa Campus on 800 m(2) surface area with no special surface cover. Temperature data were collected using thermocouples buried in soil horizontally and vertically at various distances from the pipe center and at the inlet and the outlet of the ground heat exchanger. Experimental and numerical simulation results calculated using experimental water inlet temperatures were compared. The maximum difference between the numerical results and the experimental data is 10.03%. The temperature distribution in the soil was calculated and compared with experimental data also. Both horizontal and vertical temperature profiles matched the experimental data well. Simulation results were compared with the other studies. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ground heat exchanger; Parallel pipe horizontal ground heat exchanger; Finite differences; Heat transfer; Alternating direction implicit; BURIED PIPE; MODEL; SURFACE; Thermodynamics; Energy & Fuels; Engineering; Mechanics